Enhancing sustainable urban areas through digital green infrastructure: achieving tangible outcomes - Rzayeva, Ulviyya; Balayev, Rasul; Ahmadzadeh, Emin; Mirzammadova, Konul (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this research is integrating green infrastructure into sustainable urbanization zones within the context of digitalization. The problem addressed is the difficulty of ensuring urban sustainability without considering the green infrastructure in urban and suburban areas. The article argues that city sustainability cannot be effectively addressed without integrating green corridors that connect urban and suburban zones. The research proposes using optimization and simulation models to plan and manage the expansion of green corridors in sustainable urban areas. The results highlight the importance of a joint approach to green infrastructure development in urban and suburban areas, showing that interconnectivity is crucial for long-term environmental sustainability. Findings were interpreted by illustrating how simulation models can be used to assess the effectiveness of green infrastructure in real-time. The research demonstrates that the digital modeling of green corridors enhances planning precision, ensuring better connectivity between the city and surrounding areas. The key features that solved the problem include an optimization model, which enabled efficient planning for green corridor expansion, improving connectivity between urban and suburban areas. The paper uses digital simulation tools that allow for real-time assessment of green infrastructure’s sustainability impact, leading to better-informed decision-making. The results are applicable in urban planning and sustainability management within rapidly urbanizing cities. The findings are most effective when cities have access to digital tools and aim to enhance green infrastructure’s role in sustainability strategies